Practice Configurations in Human Capital Management and Organizational Results - Medina Lorza, Aida; Acosta Naranjo, Alejandro; Revuelto Taboada, Lorenzo (Revista Venezolana de Gerencia, 2021)
Despite the growing importance that has been given to human capital as an object of research in the organizational field, at present there is still disagreement about the effects of the use of configurations of practices in its management on organizational results. For this reason, the main objective of this study is to analyze the effects of the adoption of practice configurations in human capital management on organizational results. For this purpose, a literature review is made that enables the formulation of hypotheses. Likewise, 550 self-administered questionnaires were distributed to a sample of 50 Colombian national companies, Colombian multinationals, North American multinationals and Spanish multinationals, all of them domiciled in Colombia. The data have been analyzed using the partial least squares analysis PLS-SEM or PLS path modeling. The results obtained suggest that the use of practice configurations in human capital management do not have positive effects on organizational results. It is concluded that for future studies, moderating contextual variables should be considered and said configurations of practices should be understood in the global framework of the human management system for each organization.